2021
DOI: 10.3390/biomedicines9040416
|View full text |Cite
|
Sign up to set email alerts
|

Silencing Antibiotic Resistance with Antisense Oligonucleotides

Abstract: Antisense technologies consist of the utilization of oligonucleotides or oligonucleotide analogs to interfere with undesirable biological processes, commonly through inhibition of expression of selected genes. This field holds a lot of promise for the treatment of a very diverse group of diseases including viral and bacterial infections, genetic disorders, and cancer. To date, drugs approved for utilization in clinics or in clinical trials target diseases other than bacterial infections. Although several group… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 107 publications
0
15
0
Order By: Relevance
“…The first step to make this therapy clinically possible is to chemically modify the ASOs. The modification of ASOs sugar, backbone, nucleobase, and 3′- and 5′-terminal can improve their stability, avoid nucleases attacks, and preserve target specificity [ 150 ]. ASOs modifications are mainly four: phosphorothioates (PS) linkages, locked (bridged) nucleic acids (LNA/BNA), peptide nucleic acids (PNA), and phosphorodiamidate morpholino oligomers (PMO) [ 148 ].…”
Section: Antimicrobial Alternatives Under Investigationmentioning
confidence: 99%
“…The first step to make this therapy clinically possible is to chemically modify the ASOs. The modification of ASOs sugar, backbone, nucleobase, and 3′- and 5′-terminal can improve their stability, avoid nucleases attacks, and preserve target specificity [ 150 ]. ASOs modifications are mainly four: phosphorothioates (PS) linkages, locked (bridged) nucleic acids (LNA/BNA), peptide nucleic acids (PNA), and phosphorodiamidate morpholino oligomers (PMO) [ 148 ].…”
Section: Antimicrobial Alternatives Under Investigationmentioning
confidence: 99%
“…Our previous study showed that promoter regions of the RNase III–encoding gene ( rnc ) bound and were directly regulated by the YycF ortholog gene VicR in S. mutans [ 82 ]. Antisense regulation mechanisms were used to inhibit antibiotic resistance in bacterial infections using antisense oligonucleotides [ 83 ]. Notably, an endogenous antisense RNA base paired with yycF mRNA was identified in S. aureus [ 84 ], which belongs to a trans-encoded sRNA [ 79 ].…”
Section: Targeting the S Aureus Two-component Systemsmentioning
confidence: 99%
“…Similarly, antimicrobial gene therapies, such as antisense strategy [26], transcription factor decoys [27], or CRISPR-Cas systems [28], have recently attracted enormous attention and opened new avenues to overcome multidrug resistance and restore antibiotic susceptibility. However, their therapeutic potential requires an efficient mechanism of entry of the gene agents into the bacterial cell, which is inherently a hurdle because of their poor stability, rapid clearance in blood circulation, and lack of targeting ability.…”
Section: Dissolution and Stability Enhancement Of Antimicrobial Compoundsmentioning
confidence: 99%